Self‐Assembled Asperities for Pressure‐Tunable Adhesion. Issue 5 (16th December 2022) - Deneke, Naomi; Booth, Jamie A.; Chan, Edwin P.; Davis, Chelsea S.
Abstract: Control of adhesion is important in a host of applications including soft robotics, pick‐and‐place manufacturing, wearable devices, and transfer printing. While there are adhesive systems with discrete switchability between states of high and low adhesion, achieving continuously variable adhesion strength remains a challenge. In this work, a pressure‐tunable adhesive (PTA) that is based on the self‐assembly of stiff microscale asperities on an elastomeric substrate is presented. It is demonstrated that the adhesion strength of the PTA increases with the applied compressive preload due to the unique contact formation mechanism caused by the asperities. Additionally, a contact mechanics model is developed to explain the resulting trends. For a specific PTA design, the critical pull‐off force can be increased from 0.4 to 30 mN by increasing the applied preload from 1 to 30 mN. Finally, the applicability of precision control of adhesion strength is demonstrated by utilizing the PTA for pick‐and‐place material handling. The approach in pressure‐tunable adhesive design based on self‐assembly of asperities presents a scalable and versatile approach that is applicable to a variety of material systems having different mechanical or surface properties. Abstract : Many applications require on‐demand control of adhesion at an interface without significant power consumption. In this work, a new form of adhesive termed "pressure‐tunable adhesive" (PTA) is presented. PTAs are elastomeric surfaces patterned with stiff, axisymmetric asperities. The adhesive force of the PTA increases with increasing applied preload. The pressure‐tunable adhesion is demonstrated for pick‐and‐place material handling.